Where in the world is the Philippines? debating its national territory - Severino, Rodolfo C. (Carlos P. Romulo Foundation, 2011)
Where in the world is the Philippines?' is a question that has been deftly and consistently dodged by our politicians at the expense of clearly defining the Philippines' territorial and maritime jurisdictions. Severino's scholarly work lays out what has happened in the past and what must be done in the future - and does so just as newly elected President Benigno S. Aquino begins his term in office.